A Stochastic Method for Simulating Near‐Field Seismograms: Application to the 2016 Tottori Earthquake - Pengfei Dang (American Geophysical Union (AGU), 2021)
Abstract A stochastic finite‐fault approach based on corner frequency (EXSIM) is applied to simulate the Tottori Mw 6.2 earthquake. The parameter κ0 is calculated based on ground motion recordings. Other parameters, such as quality factor (127f0.61) and stress drop (27.97 bars) are taken from our earlier work. The slip distribution refers to the results of Kubo et al. (2017, https://doi.org/10.1186/s40623-017-0714-3). The geometric spreading function and ground motion duration are taken from Atkinson and Boore (1995, https://doi.org/10.1785/bssa0850010017). The simulated results match well with the observed values in a short period (T < 1 s). In addition, the effects of hanging wall (HW) and footwall (FW) on the simulated values are discussed. The results show that the simulated results of HW stations are more consistent with the observed values than those of FW stations. The differences between simulated Pseudo Spectral Acceleration (PSA) and observed PSA with epicentral distance and azimuth are also analyzed. The results show that the local site amplification and geometric location of stations influence the simulation results for soft soil sites. Overall, the simulated ground motions obtained by applying EXSIM approach matched well with the observed recordings which could be considered as the basis for earthquake‐resistant design during the post‐disaster recovery and could become a powerful tool for earthquake ground motion prediction.